2016
DOI: 10.1371/journal.pone.0165580
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Integrity, Content, and Increased Transcript Level of Mitochondrial DNA Are Associated with Keratoconus

Abstract: Oxidative stress may play an important role in the pathogenesis of keratoconus (KC). Mitochondrial DNA (mtDNA) is involved in mitochondrial function, and the mtDNA content, integrity, and transcript level may affect the generation of reactive oxygen species (ROS) and be involved in the pathogenesis of KC. We designed a case-control study to research the relationship between KC and mtDNA integrity, content and transcription. One-hundred ninety-eight KC corneas and 106 normal corneas from Chinese patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…Compared with the Sham group, six genes (ND2, ND3, ND4L, ND5, ND6, and COX3) were upregulated in the I/R group ( p < .05, Figure ), and seven genes (ND1, ND4, COX1, COX2, ATP6, ATP8, and Cytb) were unchanged in the IR group ( p > .05, Figure ). Increasing evidence indicates that inconsistent changes in mitochondrial gene expression decrease the efficiency of ATP production (Cai et al, ; Hao et al, ; Hunter et al, ; Sun, Zong, Gao, Zhu, Tong, & Cao, ), which explains the decrease in the cellular ATP levels observed after I/R injury in this study (Figure c). Consistent with the data shown in Figure , SC1 treatment reversed the changes in mitochondrial gene expression (Figure ) and increased the cellular ATP levels (Figure c).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Compared with the Sham group, six genes (ND2, ND3, ND4L, ND5, ND6, and COX3) were upregulated in the I/R group ( p < .05, Figure ), and seven genes (ND1, ND4, COX1, COX2, ATP6, ATP8, and Cytb) were unchanged in the IR group ( p > .05, Figure ). Increasing evidence indicates that inconsistent changes in mitochondrial gene expression decrease the efficiency of ATP production (Cai et al, ; Hao et al, ; Hunter et al, ; Sun, Zong, Gao, Zhu, Tong, & Cao, ), which explains the decrease in the cellular ATP levels observed after I/R injury in this study (Figure c). Consistent with the data shown in Figure , SC1 treatment reversed the changes in mitochondrial gene expression (Figure ) and increased the cellular ATP levels (Figure c).…”
Section: Resultssupporting
confidence: 55%
“…Mitochondrial DNA encodes genes related to ATP synthesis, such as Complex I (ND1, ND2, ND3, ND4, ND4L, ND5, and ND6), Complex III (CYTB), Complex IV (COX1, COX2, COX3), and ATP synthase genes (ATP6 and ATP8) (Ott, Amunts, & Brown, ). Any persistent alteration of these mitochondrial genes affects the efficiency of ATP production (Cai et al, ; Hao et al, ; Hunter et al, ; Sun, Zong et al, ). Our results showed that the mRNA and 5hmC levels of ND2, ND3, ND4L, ND5, ND6, and COX3 were increased after ischemic injury and that these changes were reversed by the inhibition of Tet2 protein, suggesting that the cellular ATP levels are not solely dependent on the presence of O 2 but also affected by mtDNA 5hmC modification.…”
Section: Discussionmentioning
confidence: 99%
“…The similar phenotypes between SQSTM1/p62 knockdown and MRPL12 mutation provide further evidences supporting our proposal that MRPL12 may be the major downstream player in SQSTM1/p62-induced mtDNA expression. Furthermore, mitochondrial DNA transcription is known to be functionally coupled to mitochondrial biogenesis, and several components comprising mtDNA transcription apparatus concomitantly act as essential players in the process of mtDNA replication, such as mitochondrial transcription factor A (TFAM) and POLRMT ( Koc and Koc, 2012 ; Kukat et al., 2015 ; Hao et al., 2016 ). Such notion was also evidenced by our results that SQSTM1/p62-induced mtDNA expression was accompanied by elevated mitochondrial abundance ( Figures 1 K and 1M).…”
Section: Discussionmentioning
confidence: 99%
“…[41,42] The SOD1 protein neutralizes excess ROS in the cell, and ROS levels are increased in patients with KC. [43][44][45] Low levels of SOD1 enzyme can also result from gene mutations. [28] It is possible that these variants may be related to changes in the function of this gene in patients with KC, considering that these are highly conserved residues and the predicted splice sites may influence the normal processing points at the exon-intron boundaries in the gene.…”
Section: Discussionmentioning
confidence: 99%